The dynamics of personal ethics and ethical climate in public relations practitioners’ decision making - M. Safiah; A. Mohd. Hamdan; Syahruddin Ag Ahmad (Fakulti Kemanusiaan Seni dan Warisan, UMS, 2019)
This study examines the contemporary pragmatic public relations ethics that focuses on decision making to relate public relations practitioners’ ethics with their organizational ethics using Grunig and Hunt (1984) excellence theory. The aim of this study is to identify the association and the strength of the association between public relations practitioners’ ethical evaluation and ethical climate of the organization in decision-making process. This study used a structured questionnaire to measure the three different parameters in ethical evaluation (reasoning, consideration, and judgment) and the ethical climate of the organization simultaneously. The association between them is later identified from the Pearson correlation test. Respondents selected were 100 people who actively practicing public relations around Kota Kinabalu. The study revealed a positive, weak correlation as the indication that the score of ethical evaluation can but not always be used to predict the score of ethical climate. In ethically challenging decision making, one’s personal ethics is barely associated with organization’s ethical climate. Furthermore, the association shows that public relations practitioners are predominantly evaluate the situation and make ethical decision in ethical organization, though dilemmas are tempting and dragging towards unethical decision. In such inconsistency between practitioners and their organization, it is problematic because the interpersonal and organizational aspects in ethical decision making can help the organization to pursue an excellent, ethical public relations practice when addressed strategically.